PERBANDINGAN HASIL JADI KERAH SELENDANG MENGGUNAKAN BAHAN BELLINI DENGAN INTERFACING CUFNER, KAIN GULA DAN VISELIN - Elliza, Fidya; Nelmira, Weni (Akademi Kesejahteraan Sosial AKK Yogyakarta, 2023)
This research aims to: 1) Find out the finished result of a shawl collar using Bellini material with Cufner interfacing, 2) find out the finished result of a shawl collar using bellini material with sugar cloth interfacing, 3) find out the finished result of a shawl collar using bellini material with viselin interfacing, 4) find out the difference in the results of a shawl collar using bellini material and using cufner interfacing, sugar cloth and viselin. This type of research is experimental research. Data were collected using a questionnaire distributed to 18 panelists. The data analysis technique uses one-way ANOVA. The results of the research can be concluded that from the aspect of thickness, the Cufner average is 4.22; sugar cloth 3.56; viselin 2.78. Judging from the stiffness aspect, the Cufner average was 3.94; sugar cloth 3.78; viselin 3.22. Judging from the aspect of surface flatness, an average Cufner of 4.78 was obtained; sugar cloth 4.17; viselin 3.89. Judging from the aspect of shape stability, the Cufner average was 4.56; sugar cloth 3.67; viselin 3.56. Overall, the significance value obtained is 0.000, which is smaller than 0.05, which means there is a significant difference in the results of the finished shawl collar using bellini material with the use of cufner interfacing, sugar cloth and viselin